EVALUASI PENYESUAIAN TARIF DASAR PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN PURBALINGGA - Suliyanto, Suliyanto (Performance, 2010)
Conditions of macroeconomic, increase of equipment/piping price, chemicals, generators operating costs and tax of groundwater affect to operational costs PDAM Kabupaten Purbalingga, hence the need for tariff adjustments. Analysis tools used in this study is the Break Even Point (BEP) in accordance with the Permendagri Number 02 Year 1998 About the Guidelines on Water Tariff Determination The Regional Water Company. Based on the analysis results that basic tariff PDAM Purbalingga is Rp. 1261 per m3, so that PDAM Kabupaten Purbalingga needs to adjust rates by taking into account the level of ability to pay from their customers. Tariff adjustments must be accompanied by an increase in service to customers, thus increasing customer sacrifices will be balanced by an increase in the value (service) from PDAM Kabupaten Purbalingga.